Autoimmunity vs autoinflammation in Behcet's disease: do we oversimplify a complex disorder? - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2006)
Behcet's disease (BD) is a systemic inflammatory disorder with a diverse spectrum of clinical manifestations including mucocutaneous, ocular, vascular, gastrointestinal, musculoskeletal and central nervous system involvement [1]. A complex genetic background leading to a pro-inflammatory, innate-immune-system-derived activation perpetuated by adaptive immune responses against enviromental and auto-antigens is accepted to be the hallmark of BD [2]. This review aims to make an in-depth critical analysis of current data for recent controversies on the role of innate immune system vs autoimmunity in BD [3-5].
Keywords: Behcet's disease; innate; adaptive; pathogenesis; HEAT-SHOCK PROTEINS; MONOSODIUM URATE CRYSTALS; T-CELL RESPONSES; DENDRITIC CELLS; PEPTIDE 336-351; ANTIGEN; UVEITIS; GAMMA; SKIN; IDENTIFICATION